No-cook cookbook - Theodorou, Susie (Hardie Grant North America, 2024)
"No-Cook Cookbook will teach you to fill your fridge with fresh ingredients and ready-to-eat protein like cold cuts or tinned fish that can easily be turned into budget-friendly family meals or casual dinners for one or two. Whether you're avoiding the oven on a hot night, working without a full kitchen, or just not that into cooking from scratch tonight, No-Cook Cookbook is here to save the day." -- Amazon.